Promotion of terrace cultivation of vegetables by urban housewives- an action research - Sreedaya G S (Department of Agricultural Extension, College of Agriculture, 2004)
The study which intended to promote production of safe, hygienic and ecofriendly vegetables through the cultivation on house terraces was conducted among the urban housewives. Thirty randomly selected housewives of Poojapura Ward of Thiruvananthapuram Corporation were the respondents. In the first phase of action research, two separate trainings were conducted. The training programme was scheduled in accordance with the result of the training need analysis conducted among the respondents. The training programme included illustrated lecture classes and method demonstrations on various aspects of terrace cultivation of vegetables by the researcher and experts and field visit to different terrace gardens. Inputs like sacks, seeds and organic manures were distributed to the trainees in the concluding session of the training programme. The respondents started cultivation on their house terraces and continued for two seasons under the strict monitoring and supervision of the researcher. Seventy five per cent of the respondents continued cultivation while 25 per cent of them had withdrawn due to inevitable personal reasons. It was found out that there was a positive change in the knowledge and attitude of respondents after the training programme. Majority of the respondents were high adopters of different cultivation practices on vegetable cultivation. On an average, they spend eight hours (34 %) of their time in kitchen duties and one hour (4 %) in their terrace gardens. The study also revealed that the consumption pattern of vegetables by the urban family had increased by 1.70 kg per week and a reduction in the quantity of vegetables purchased was also reported. It was also found out that 97 per cent of the respondents had a cost-benefit ratio of greater than two and only three per cent of respondents were reported to have a low cost-benefit ratio of less than one. Spread effect ratio was found to be 1 : 11 : 2. The study had certain implication towards the field of agriculture, health, hygiene, nutrition and empowerment. Vermicomposting was found not only a means for garbage disposal, but also, it was a means for producing enough organic manures for the vegetables. Azolla, which is a floating fern was found to be an effective organic manure, poultry feed, cattle feed and mosquito repellant. Terrace cultivation of vegetables facilitated a reduction in the purchase of vegetables at the rate of Rs. 25 per week and increase in the consumption of vegetables at the rate of 1.7 kg per week. It is one of the best method for horticultural therapy through which mentally retarded children could be brought to the mainstreams of life. In addition, terrace cultivation of vegetables is also a means of empowerment of the residents of old age home and the students of orphanage schools. With the evidence of the study, the researcher recommends 65-70 sacks in an area of 1000 square feet. The researcher also recommends different types of vegetables in order to attain the vegetable self-sufficiency from the terrace itself for a family having four members of which two are children below the age of 10 years. Above all terrace cultivation of vegetables provided an invaluable feeling of satisfaction through the production of safe, hygienic and eco-friendly vegetables at low cost on house terrace itself and provide nutritional security to the households.